2020
DOI: 10.3390/ijerph17239134
|View full text |Cite|
|
Sign up to set email alerts
|

Dengue Seroprevalence and Seroconversion in Urban and Rural Populations in Northeastern Thailand and Southern Laos

Abstract: Dengue is the most rapidly spreading mosquito-borne viral disease in the world. The detection of clinical cases enables us to measure the incidence of dengue infection, whereas serological surveys give insights into the prevalence of infection. This study aimed to determine dengue seroprevalence and seroconversion rates in northeastern Thailand and southern Laos and to assess any association of mosquito control methods and socioeconomic factors with dengue virus (DENV) infection. Cross-sectional seroprevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(29 citation statements)
references
References 44 publications
1
20
2
Order By: Relevance
“…The age-specific DENV seroprevalence in this study demonstrated a gradual increasing trend as age advanced. This was in line with other DENV seroprevalence studies conducted locally and internationally, which found an increment in DENV seropositivity rate with increasing age [ 1 , 11 , 13 , 26 , 36 , 40 ]. This observation was expected, as the longer a person resides in a dengue-endemic area, the greater the risk one is exposed to dengue infection coupled with the lifelong persistence of anti-DENV antibodies [ 1 , 13 , 34 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The age-specific DENV seroprevalence in this study demonstrated a gradual increasing trend as age advanced. This was in line with other DENV seroprevalence studies conducted locally and internationally, which found an increment in DENV seropositivity rate with increasing age [ 1 , 11 , 13 , 26 , 36 , 40 ]. This observation was expected, as the longer a person resides in a dengue-endemic area, the greater the risk one is exposed to dengue infection coupled with the lifelong persistence of anti-DENV antibodies [ 1 , 13 , 34 ].…”
Section: Discussionsupporting
confidence: 91%
“…Population movement could have influenced the DENV seroprevalence results, lowering the seroprevalence rate if many migrants were coming from less dengue-prone areas [ 32 ]. Compared with other dengue-endemic Southeast Asian countries, the seroprevalence rate in this study was higher than that found in Singapore [ 33 , 34 ], while countries such as Thailand, Laos, and the Philippines reported even higher rates [ 35 , 36 ]. Compared to Latin American countries, which are also endemic with dengue, the DENV seroprevalence rate was comparable to two other cities, namely São Paulo, Brazil [ 37 ] and Maracay, Venezuela [ 38 ], but was lower than that of another community study conducted in Columbia [ 39 ].…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…There was an error in the original article [ 1 ]: ethylenediamine tetraacetic acid (EDTA)-tubes was stated incorrectly.…”
Section: Text Correctionmentioning
confidence: 99%
“…The dense human populations of urban areas increase vector-human contact, and dengue virus (DENV) circulates more efficiently [ 2 ]. However, recent seroprevalence studies showed that rural populations have been exposed to DENV as much as urban populations [ 4 , 5 ]. The high seropositive rate in rural areas is likely due to an increase of mobile populations infected with DENV from urban areas, and transitions of rural areas toward urban areas.…”
Section: Introductionmentioning
confidence: 99%